2022
DOI: 10.1029/2022jb024776
|View full text |Cite
|
Sign up to set email alerts
|

Continental Reworking in the Eastern South China Block and Its Adjacent Areas Revealed by F‐J Multimodal Ambient Noise Tomography

Abstract: The South China Block (SCB), which is located in the southeastern part of the Eurasian plate, is generally believed to have developed during the early Neoproterozoic era due to the amalgamation of the Cathaysia Block to the southeast and the Yangtze Craton to the northwest (Figure 1a, Y. Wang et al., 2013). In the Triassic, the SCB collided with the North China Craton (NCC), generating the well-known high and ultrahigh-pressure (HP and UHP) metamorphic belts that constitute the Qinling-Dabie orogen (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 98 publications
(327 reference statements)
0
2
0
Order By: Relevance
“…(2020) extracted higher‐mode dispersion curves from multiple regions of the USArray; Chen et al. (2022), Fu et al. (2022) and Zhan et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) extracted higher‐mode dispersion curves from multiple regions of the USArray; Chen et al. (2022), Fu et al. (2022) and Zhan et al.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Wang et al (2019) proposed an array-based method (the frequency-Bessel transform method, abbreviated as the F-J method) to obtain the higher-mode Rayleigh wave dispersion from NCFs. Subsequently, a series of higher-mode surface wave studies were conducted based on this method: Li and Chen (2020) extended this method to earthquake surface waves; Hu et al (2020) applied this method to Love waves; Wu et al (2020) extracted higher-mode dispersion curves from multiple regions of the USArray; Chen et al (2022), Fu et al (2022) and Zhan et al (2020) used this method to image the three-dimensional Vs structure in Southeast China, Long Beach and Northeast China, respectively; Li, Shi, and Chen (2021) and Li et al (2022) observed leaking mode dispersion curves by using this method.…”
mentioning
confidence: 99%